Ba0.5Sr0.5Co0.8Fe0.2O3-delta-Sc0.1Zr0.9O1.95 composite cathode on zirconia based electrolyte for intermediate temperature solid oxide fuel cells - Lee, Seong Oh; Lee, Daehee; Jung, Inyong; Kim, Dongha; Hyun, Sang-Hoon; Kim, Joosun; Moon, Jooho (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
We synthesized Ba0.5Sr0.5Co0.8Fe0.2O3-delta (BSCF) powders with a primary particle size of 20 nm using a Pechini type method. By using nanocrystalline BSCF powders, we were able to fabricate a ceria interlayer-free nanoporous cathode on a scandia stabilized zirconia (ScSZ) electrolyte at low temperatures. Cathodes sintered below 750 degrees C lacked sufficient mechanical adhesion to the electrolyte, while electrode was well adhered to the electrolyte when fired at 800 degrees C. The symmetrical BSCF-ScSZ vertical bar yttria stabilized zirconia (YSZ)vertical bar BSCF-ScSZ half-cell that we generated had an exceptionally low polarization resistance of 0.06 Omega.cm(2) at 700 degrees C. The maximum power density of the BSCF-ScSZ vertical bar ScSZ vertical bar Ni-ScSZ unit cell was over 1 W cm(-2) at 700 degrees C. We investigated the durability of the BSCF-ScSZ composite cathode by 30 thermo-cycles performed by varying the temperature from 200 to 700 degrees C. The polarization resistance after the test remained low at less than 0.08 Omega.cm(2). Copyright (C) 2013, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: PERFORMANCE; PEROVSKITE; SOFCS; IMPEDANCE